2022
DOI: 10.3389/fmicb.2022.1039884
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Yujin Powder alcoholic extracts on ILC3s-TD IgA-colonic mucosal flora axis of DSS-induced ulcerative colitis

Abstract: The intestinal flora maintained by the immune system plays an important role in healthy colon. However, the role of ILC3s-TD IgA-colonic mucosal flora axis in ulcerative colitis (UC) and whether it could become an innovative pathway for the treatment of UC is unknown. Yujin Powder is a classic prescription for treatment of dampness-heat type intestine disease in traditional Chinese medicine and has therapeutic effects on UC. Hence, the present study aimed to investigate the regulatory mechanism of Yujin Powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…IRF4 can suppress the expression of Bcl6 27 . Bcl6 is aberrantly expressed in mesenteric lymph nodes of colon in UC mice 28 . In order to investigate whether IRF4 participates in the regulation of Bcl6, GST‐pull down and Co‐IP assays were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IRF4 can suppress the expression of Bcl6 27 . Bcl6 is aberrantly expressed in mesenteric lymph nodes of colon in UC mice 28 . In order to investigate whether IRF4 participates in the regulation of Bcl6, GST‐pull down and Co‐IP assays were performed.…”
Section: Resultsmentioning
confidence: 99%
“…27 Bcl6 is aberrantly expressed in mesenteric lymph nodes of colon in UC mice. 28 In order to investigate whether IRF4 participates in the regulation of Bcl6, GST-pull down and Co-IP assays were performed. Co-IP assay indicated that both IRF4 and Bcl6 immunoblot was observed in the input group and IP group but not the negative control IgG group (Figure 5A).…”
Section: Irf4 Negatively Regulates Bcl6mentioning
confidence: 99%
“…22 On the As shown in the timeline overview in Figure 5B, the clusters that appeared during 2008-2014 and later during 2015-2023 demonstrated that with the passage of time, the hotspot of research has shifted from the earlier research on pathogenesis, clinical research on TCM for treating IBD, and research on pharmacological mechanisms of action related to the regulation of inflammatory factors through signaling pathways, adjuvant therapy research in treating IBD, to network pharmacology, research on pathogenesis related to intestinal flora, and the mechanism of action of Chinese medicine. [27][28][29][30][31] Among these clusters, #3 Jianpi Qingchang decoctin and #1 Qing-dai had a relatively long time span, indicating that the clinical research on the treatment of IBD by TCM had received extensive attention. The largest cluster was #0 Network pharmacology, which indicated that researchers had a strong interest in this topic.…”
Section: Keyword Analysismentioning
confidence: 99%
“…The expression of IgA levels in colon further aggravated colon mucosa. Alcoholic extracts of Yujin Powder could ameliorate UC through upregulating the proportion of ILC3s and expression of MHC II, enhancing the inhibition of ILC3s on Tfh cells, further regulating IgA response and IgA targeted colonic mucosal flora ( Wen et al, 2022 ). Ran et al also demonstrated that Prunus humilis Bunge [Rosaceae; pruni semen] improved the expression of SIgA related genes and further regulated intestinal mucosal immune function.…”
Section: Repairing the Intestinal Immune Barriermentioning
confidence: 99%
“…The expression of IgA levels in colon further aggravated colon mucosa. Alcoholic extracts of Yujin Powder could ameliorate UC through upregulating the proportion of ILC3s and expression of MHC II, enhancing the inhibition of ILC3s on Tfh cells, further regulating IgA response and IgA targeted colonic mucosal flora (Wen et al, 2022)…”
Section: Evidence On Tcm Formula Targeting Intestinal Immune Barriermentioning
confidence: 99%